CO2 Consequences of Oil and Bio-fuel Saving Measures at a Swedish Pulp and Board Mill - Ek, Eva-Lena (My University, 2001)
The master thesis project consists of two parts. Part one considers the cost-effectiveness of reducing carbon dioxide emissions from a Swedish pulp and board mill, using oil as fuel. Environmentally harmful effluents need to be pre-evaporated before being evaporated and combusted with the black liquor in the recovery boiler. Conventional pre-evaporation technology uses live steam as a heat source. Identifying and using excess heat for pre-evaporation and heat pumping will decrease the live steam and thereby oil demand of the factory. Annual costs and CO2 emissions of different retrofitting alternatives are compared to costs and emissions of the references using live steam under varying electricity price, CO2 tax and reference electricity system. The result of the study show that reduction of CO2 emissions does not lead to increased costs. The pre-evaporation system emitting the least is also the cheapest regardless of electricity price and CO2 tax, due to lower fuel costs. The live steam reducing measures considered lower the CO2 emissions by between 40 000 and 60 000 tonnes per year compared to the pre-evaporation system running on live steam. The relative annual profits are then between 16 and 29 MSEK. The annual cost of the reference systems add between 35 and 50 MSEK to the current cost.The reference emissions are between 20 and 60 ktonnes per year compared to the current emissions of the mill. In a second part of the project the same measures are applied to a hypothetical case where the mill uses only bio-fuel for its live steam and electricity production. The low life cycle emissions of bio fuel make it impossible for the Skoghall mill to reduce its emissions by decreasing the fuel demand. The system boundaries must be extended to include another application where the released bio fuel can replace fossil fuel. In the study, a co-operating plant is supposed to switch from oil to bio-fuel on condition that the mill can provide bio fuel to a lower price than the market price. The factory is assumed to use the bio-fuel either for heat or combined heat and power production. CO2 tax, electricity price and reference electricity systems were varied in the study just as in the oil case described above. Due to the low bio-fuel price, reduction of the live steam requirement is not as beneficial for the mill as in the oil case. At high electricity prices it would in many cases be more beneficial to have a high electricity production enabled by the larger live steam demand of the reference pre-evaporator system. No bio-fuel is released if the reference system is built, and co-operating with the other plant will not be possible. In those cases when releasing bio-fuel at Skoghall did lead to lower annul costs, co-operating with the other plant enabled CO2 emission reduction at the other plant at lower costs than without co-operation. The specific cost of CO2 emission reduction in the CHP case were lower than 100 SEK/tonne when the plants worked together, and the decrease was more than 60 000 tonnes per year. The CO2 emission reductions due to reduced oil demand in the first part of the study is economically beneficial for the mill, even with today’s environmental policies. The reduction enabled by co-operation in the case when bio-fuel is used needs new environmental politicy instruments, however. If no restriction was put on the mill to lower the CO2 emissions, the co-operation would not take place, and the result would be unchanged or increased emissions from the mill and unchanged emissions from the oil boiler at the other plant.
Keywords: Kemiteknik; Chemical Engineering